Nanoparticle-Based Therapies for Turning Cold Tumors Hot: How to Treat an Immunosuppressive Tumor Microenvironment - Giustarini, Giulio; Pavesi, Andrea; Adriani, Giulia (Frontiers in Bioengineering and Biotechnology, 2021)
Nanotechnologies are rapidly increasing their role in immuno-oncology in line with the need for novel therapeutic strategies to treat patients unresponsive to chemotherapies and immunotherapies. The tumor immune microenvironment (TIME) has emerged as critical for tumor classification and patient stratification to design better treatments. Notably, the tumor infiltration of effector T cells plays a crucial role in antitumor responses and has been identified as the primary parameter to define hot, immunosuppressed, excluded, and cold tumors. Organic and inorganic nanoparticles (NPs) have been applied as carriers of new targeted therapies to turn cold or altered (i.e., immunosuppressed or excluded) tumors into more therapeutically responsive hot tumors. This mini-review discusses the significant advances in NP-based approaches to turn immunologically cold tumors into hot ones.